Security Analysis of Diffie-Hellman Algorithm in Cryptographic Key Exchange - Jeni Nova Situmoran; Eunike Nainggolan; Adelwin Saputra Loi; Andreas Wendi Hutablian; Anju Franjein Hutasoit (Jurnal Teknik Indonesia, 2023)
The Diffie-Hellman algorithm is a cryptographic method used for secure key exchange between two parties over an insecure channel. This study aims to analyze the implementation of the Diffie-Hellman algorithm, focusing on its security and efficiency aspects. The research process begins with manual step-by-step calculations of this algorithm, including prime number selection, modulus calculation, and key exchange. Furthermore, key encryption and decryption tests are carried out to assess the algorithm's resilience to threats. Although this algorithm has proven effective in protecting data, the efficiency of the encryption and decryption processes can be affected by the size of the key used. The test results show that Diffie-Hellman can maintain the confidentiality of communications well, although its processing speed may be affected in systems with large-scale requirements. This study concludes that the Diffie-Hellman algorithm is suitable for use in communications that require a high level of security, but its efficiency needs to be optimized by considering factors such as key size and algorithm optimization. These findings provide important insights for the development of cryptography-based security systems for modern communication applications.